2005
DOI: 10.1016/j.resp.2005.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to NT-3 attenuates cholinergic nerve-mediated contractions in cultured murine airways

Abstract: Prolonged exposure to NT-3 attenuates cholinergic nerve-mediated contractions in cultured murine airways.Bachar, Ofir; Adner, Mikael; Uddman, Rolf; Cardell, Lars-Olaf General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Furthermore, mice and human airways may differ in neurotrophin effects. On the other hand, our data with NT3 in human ASM are consistent with those of Bachar et al (2) on NT3 decrement of force in mouse trachea.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, mice and human airways may differ in neurotrophin effects. On the other hand, our data with NT3 in human ASM are consistent with those of Bachar et al (2) on NT3 decrement of force in mouse trachea.…”
Section: Discussionsupporting
confidence: 93%
“…*Significant difference from control (P Ͻ 0.05). that prolonged NT3 exposure of mouse trachea diminished the responsiveness to electric field stimulation in vitro (2). The findings in our study of BDNF, NT3, and NT4 expression suggest that, even under normal conditions, ASM-derived neurotrophins may have an autocrine or paracrine effect; however, trkB and trkC expression may also allow ASM to react to neurotrophins derived from other sources such as neurons or immune cells.…”
Section: Discussionmentioning
confidence: 50%
“…However, EFS elicited contractions in tracheal preparations of mice in previous studies [32], and in line with that we observed neurally evoked bronchoconstriction in murine PCLS at higher electric fields (figure 2). In sheep PCLS, on the other hand, airways were highly excitable (figures 1, 3) and nerve activation was observed already at low frequencies or even after one single electrical stimulus (0.4 Hz at train width 2.5 s).…”
Section: Discussionsupporting
confidence: 93%
“…Electric field stimulation (EFS) was used to access nerve-induced contractions, and carried out according to previous protocols (Bachar et al, 2005a). Tracheal segments were stimulated with EFS by two electrodes placed at opposite sides of the tracheal segments (Current Stimulator Model CS200, J.P. Trading, Aarhus, Denmark).…”
Section: Electric Field Stimulationmentioning
confidence: 99%